2019
DOI: 10.1136/bmjopen-2018-025783
|View full text |Cite
|
Sign up to set email alerts
|

Making headlines: an analysis of US government-funded cancer research mentioned in online media

Abstract: ObjectiveTo characterise how online media coverage of journal articles on cancer funded by the US government varies by cancer type and stage of the cancer control continuum and to compare the disease prevalence rates with the amount of funded research published for each cancer type and with the amount of media attention each receives.DesignA cross-sectional study.SettingThe United States.ParticipantsThe subject of analysis was 11 436 journal articles on cancer funded by the US government published in 2016. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 29 publications
(20 reference statements)
7
18
1
Order By: Relevance
“…The study extends the work of Maggio et al that identified patterns and frequencies of how 200264 scholarly studies about cancer circulated through mass media (e.g., press releases from news wires, non-profit and governmental media organisations, news aggregators and journalistic news organisations) [30]. Maggio et al found that the frequency of journal articles about specific cancer types was misaligned with US rates of cancer burden (i.e., incidence and mortality) [30]. However, the researchers did not examine the alignment of journal articles specifically with journalistic news coverage, a popular [12][13][14]80] and more direct way the public accesses health information.…”
Section: Plos Onesupporting
confidence: 67%
See 3 more Smart Citations
“…The study extends the work of Maggio et al that identified patterns and frequencies of how 200264 scholarly studies about cancer circulated through mass media (e.g., press releases from news wires, non-profit and governmental media organisations, news aggregators and journalistic news organisations) [30]. Maggio et al found that the frequency of journal articles about specific cancer types was misaligned with US rates of cancer burden (i.e., incidence and mortality) [30]. However, the researchers did not examine the alignment of journal articles specifically with journalistic news coverage, a popular [12][13][14]80] and more direct way the public accesses health information.…”
Section: Plos Onesupporting
confidence: 67%
“…It explores the intertwining hierarchy among an online collection of 86 traditional and digitalnative news publications and their role in disseminating cancer research funded by the US government to the public. The study extends the work of Maggio et al that identified patterns and frequencies of how 200264 scholarly studies about cancer circulated through mass media (e.g., press releases from news wires, non-profit and governmental media organisations, news aggregators and journalistic news organisations) [30]. Maggio et al found that the frequency of journal articles about specific cancer types was misaligned with US rates of cancer burden (i.e., incidence and mortality) [30].…”
Section: Plos Onesupporting
confidence: 66%
See 2 more Smart Citations
“…These stories were identified based on a listing of 2016 news stories that featured links to cancer research that was compiled by the author team for an earlier study. 20 From this listing, we focused on news stories reporting on e-cigarettes and the HPV vaccine as these two topics have been previously identified as relevant areas of cancer prevention among parents of adolescents. 21 The two specific stories were selected for their inclusion because they contained links to journal articles, were published in two online news sources with national readership and were both less than 1000 words in length.…”
Section: Data Collectionmentioning
confidence: 99%